Leaders’ Thinking Styles And Impacts In Strategic Momentum: Pilot Study Of University Leaders’ Opinions In Karbala University - Alhimyari, Bashar Abbas; Aljanabi, Adil Abbas Abed (The journal of contemporary issues in business and government, 2021)
The paper aims to examine the impact of leaders’ thinking styles in strategic momentum, an oversample of 72 administrative leaders at the University of Karbala. The information related to practical aspect was collected by a survey designed according to Grigorenko& Sternberg, 1997 matrix to measure thinking styles, while Peters et al, 2018 matrix were leveraged to measure Strategic Momentum. Forms information was subjected to several statistical methods and leveraged SPSS, V23. One of the most important conclusions that the University of Karbala leaders adapt several thinking styles with deferent scores, as Hierarchic Style is the most influential in strategic momentum.